Risk identification and assessment of infrastructure development for projects’ valuation / S. S. Shaffie, S. H. Jaaman and D. Mohamad - Shaffie, S. S.; Jaaman, S. H.; Mohamad, D. (Universiti Teknologi MARA, Perak, 2018)
Public capital investment in infrastructure development holds the key for national economic growth. It includes the development of roads, power plant, ports, railways and other public facilities. The developments are important to provide better condition and services for the people and economic activities. Investment in public infrastructures demand high spending, long term commitment and involves with numbers of risks. In order to reduce government financial liabilities, many countries adopted built-operate-transfer (BOT) scheme. BOT is an agreement between the public and private sectors where the private sector required to finance, design, build, operate and maintain the facility. In return, private sector can collect profit from users whom benefited the facility for a certain period called concession period. However, the development of public infrastructures with BOT are tangled with numbers of risk. Without systematic risk management, the project will fail and disrupt huge monetary impact. The objective of this study is to identify risk anticipated in public infrastructure development in Malaysia. Risks are identified from previous studies done in Malaysia and other countries. The identified risks are assessed to determine severity impact of the risks on projects’ valuation.